Research Notes. CORPORATE SOCIAL RESPONSIBILITY AND STOCK MARKET PERFORMANCE. - Alexander, G. J.; Buchholz, R. A. (Academy of Management Journal, 1978)
The article examines the relationship between social responsibility and stock market performance of corporations in the U.S. for the period 1970-1974. Risk measures and differential returns of the ...